Transformaciones productivas del corregimiento de Santa Elena, basada en las dinámicas territoriales rurales y la prestación de servicios ecosistémicos (2021)
The district of Santa Elena, the place chosen for the investigation, is located in the municipality of Medellìn and is part of the 5 districts of said municipality. Where an analysis of productive transformation in the sidewalks (Placer, Placer and Plan) of the township is proposed based on the rural territorial dynamics of the areas and the benefits of ecosystem services. In such a way that guidelines are established for the management of sustainable agriculture and adequate land use planning that favors the quality of life of peasant populations. Likewise, the reduction of poverty and inequality be strengthened for the village populations studied. It is important to emphasize the use of Participatory Rural Diagnosis tools, developed by FAO, where a series of parameters are proposed that manage to collect information on the rural populations studied, their families and the state of crop production. From the survey of cartographic information that was obtained from government sources such as the DATA BASE of the Medellín Mayor's Office, where a shapefile of the base map of the township, rural land use, ecological connectivity and own elaboration of maps of crops suitable for processes was collected. of agricultural reconversion. Each of these shapefiles were processed in the ArcGis tool based on the data base sources of the Alcadia de Medellìn. Once the information was collected and processed in ArcGis, it was pertinent to generate agroecological guidelines that manage to identify an adequate social, economic and environmental diagnosis of the productive sector (cultivation). After said diagnosis, it will yield certain results and will allow to analyze if the process is viable for reconversion and promotion of sustainable agriculture